KEMAMPUAN MENULIS BAGIAN HASIL PENELITIAN DAN PEMBAHASAN ARTIKEL HASIL PENELITIAN - Dina Nurul Arofah (Universitas Bengkulu, 2018)
The purpose of this research is to know the result of research part and article discussion of postgraduate students of education in Indonesian language. The analyzed data is work sheet of students of education in Indonesian language in result article of thesis research. The data resoursh is gained by document taking of scientific article in study Program. The finding of the research are; the ability of writing scientific article writing in research result and discussion of postgraduate student of Pneidikan bahasa infonesia is in very good level with average 88,6. The scoring in each step is, (1) moves-1 (information of research) has qualification 95,5%, (2)Moves-2 (statement of result) has qualification 100 %, (3) Moves-3 (statement of unexpected research result ) has qualification 83,3%, (4) Moves-4 (using of reference of previous research) has qualification 86,7%, (5) Moves-5 (statement of reseach result) has qualification 100 %, (6) Moves-6 (illustration to support result of research) has qualification 87,5%, (7) Moves-7 (writer interpretation towards research finding) has qualification 79,2%, (8) Moves-8 ( writer suggestion as practice implementation of research finding) has qualification 62,5%. Thus, the ability to write a scientific article part research results and discussion of graduate students of education in Indonesia is in the category very well that is 88.6.Keywords : ability, writing, the result of research part and article discussion